Preferential location of prilocaine and etidocaine in phospholipid bilayers: A molecular dynamics study - Pickholz, Monica; Fraceto, Leonardo Fernandes [UNESP]; de Paula, Eneida (Elsevier B.V. Sa, 2009)
In this work, we report a 20-ns constant pressure molecular dynamics simulation of the uncharged form of two amino-amide local anesthetics (LA). etidocaine and prilocaine, present at 1:3 LA:lipid, molar ratio inside the membrane, in the hydrated liquid crystal bilayer phase of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine (POPC). Both LAs induced lateral expansion and a concomitant contraction in the bilayer thickness. A decrease in the acyl chain segment order parameter, -S(CD), compared to neat bilayers, was also observed. Besides, both LA molecules got preferentially located in the hydrophobic acyl chains region, with a maximum probability at similar to 12 and similar to 10 angstrom from the center of the bilayer for prilocaine and etidocaine, respectively. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Molecular dynamics; Local anesthetics, Lipid membrane; Order parameter